1984
DOI: 10.1007/bf00286607
|View full text |Cite
|
Sign up to set email alerts
|

Regional mapping of clotting factors VII and X to 13q34. Expression of factor VII through chromosome 8

Abstract: Blood clotting factors were investigated in a patient with trisomy 8 mosaicism, a patient with an r(13), and a patient with distal trisomy 13q. Results are compatible with the assignment of the structural genes of factors VII and X to 13q34 and the existence of a regulatory mechanism associated with chromosome 8 controlling the expression of factor VII alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…The present results of an about 50~ deficiency of F7 and F10 in Cases 1 and 2 confirms previous observations that the structual genes of F7 and FI0 are located on the long arm of chromosome 13 (13q34) (Pfeiffer et al, 1982;de Grouchy et al, 1984;Ott and Pfeiffer, 1984).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results of an about 50~ deficiency of F7 and F10 in Cases 1 and 2 confirms previous observations that the structual genes of F7 and FI0 are located on the long arm of chromosome 13 (13q34) (Pfeiffer et al, 1982;de Grouchy et al, 1984;Ott and Pfeiffer, 1984).…”
Section: Discussionsupporting
confidence: 92%
“…Pfeiffer et al (1982), de Grouchy et al (1984 and Ott and Pfeiffer (1984) reported patients of 13q34 deletion affected with deficiency of F7 and F10 activity. We analyzed activity and antigen of F7 and F10 in 5 patients with abnormal chromosome 13.…”
Section: Ntroductionmentioning
confidence: 99%
“…The FVII gene is located on chromosome 13 (13q34-qter), next to the FX gene, 13,14 and comprises 9 exons and 8 introns. 15 A polymorphic minisatellite, consisting of a variable number of 37-nucleotide tandem repeats, spans the 3Ј end of exon 7 and the 5Ј portion of intron 7, 7 and the first repeat contains the donor splice site for the excision of intron 7.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, her cytogenetic findings were informative in determining the localization of these coagulation factor genes at the subband level. The combination of various al., 1984;Gilgenkrantz et al, 1986). Although overt deletion of the long arm Vol.…”
Section: Mapping Of Genes Encoding Coagulation Factors VIImentioning
confidence: 99%
“…Subsequent investigations on patients with various abnormalities of chromosome 13 have confirmed that monosomy for the 13q34 segment produced a 50~ decrement (de Grouchy et al, 1984;Gilgenkrantz et al, 1986;Fukushima et al, 1987) while trisomy for the same segment led to a 50~ increment (Gilgenkrantz et al, 1986) in plasma FVII and FX levels. In addition, Scambler and Williamson (1985) have demonstrated on Southern blot analysis of DNA from patients with monosomy for 13q34 using a cloned human F10 gene that the low ,expression of FX resulted from loss of one copy of the F10 structural genes.…”
mentioning
confidence: 93%